The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1161/circulationaha.114.010070
|View full text |Cite
|
Sign up to set email alerts
|

Age at Menarche and Risks of Coronary Heart and Other Vascular Diseases in a Large UK Cohort

Abstract: Background-Early menarche has been associated with increased risk of coronary heart disease (CHD), but most studies were relatively small and could not assess risk across a wide range of menarcheal ages; few have examined associations with other vascular diseases. We examined CHD, cerebrovascular disease, and hypertensive disease risks by age at menarche in a large prospective study of UK women. Methods and Results-In 1.2 million women (mean±SD age, 56±5 years) without previous heart disease, stroke, or cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
201
5
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(218 citation statements)
references
References 32 publications
10
201
5
2
Order By: Relevance
“…The reference group in all analyses comprised those with an age at menarche of 12 to 13 years. There is some variation across studies in the definition of early menarche (≤10, ≤11, or ≤12 years) and late menarche (≥14, ≥15, or ≥16 years), likely influenced by the size and information available in the specific study, but our categorization is in line with commonly used cutoff values 4, 5, 6, 7, 8, 10, 11, 14, 16…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference group in all analyses comprised those with an age at menarche of 12 to 13 years. There is some variation across studies in the definition of early menarche (≤10, ≤11, or ≤12 years) and late menarche (≥14, ≥15, or ≥16 years), likely influenced by the size and information available in the specific study, but our categorization is in line with commonly used cutoff values 4, 5, 6, 7, 8, 10, 11, 14, 16…”
Section: Methodsmentioning
confidence: 99%
“…In line with these findings, there is some but less consistent evidence of an association between age at menarche and cardiovascular disease (CVD) events 12, 16, 17, 18. Mendelian randomization studies suggest causal effects of greater childhood BMI on early timing of menarche and of earlier menarche on higher adult BMI and CVD risk,19, 20 although genetic pleiotropy may at least partially explain these findings 12.…”
mentioning
confidence: 99%
“…In Japan, the mean age at menarche decreased from 13.2 years in 1961 to 12.2 years in 2011 in school‐aged girls1. Earlier‐onset menarche is reported to be associated with obesity2, 3, 4, 5, type 2 diabetes mellitus4, 6, 7, 8, 9, 10, 11, cardiovascular disease4, 12, 13, 14, breast cancer15 and increased all‐cause mortality4, 13, 16, 17, 18. It is therefore possible that age at menarche can provide important information to help prevent non‐communicable diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The association between early menarche and all-cause mortality is relatively consistent [6] . However, the association between early menarche and cardiovascular diseases, especially stroke, has not been well investigated [6][7][8] . It has been demonstrated that early menopause has a modest effect on cardiovascular diseases [9] .…”
Section: Introductionmentioning
confidence: 99%